Monetary policy with heterogeneous households and financial frictions - Jae Won Lee (Rutgers University, Department of Economics, 2010)
This paper presents and estimates a sticky-price model with heterogenous households and financial frictions. Frictions in state-contingent asset markets lead to imperfect risksharing among households with idiosyncratic labor incomes. I study the impacts of the introduced financial frictions on optimal monetary policy by documenting implications for the central bank's objective function, the equation that characterizes inflation-output gap trade-offers, targeting rules, interest rate rules, and welfare of the economy. Employing the estimated model, the paper argues that the central bank should place a stronger emphasis on stabilizing inflation than it has, and failing to do so can generate nontrivial welfare costs.
Keywords: 330; Geldpolitik; Preisrigidität; Finanzmarkt; Unvollkommener Markt; New-Keynesian Phillips Curve; Theorie